Avaliação de desempenho do microaspersor amanco em bancada de testes - Mazzer, Helton Rogério; Pletsch, Talita Aparecida [UNESP]; Cruz, Raimundo Leite [UNESP]; Vilas Boas, Márcio A.; de Oliveira, Érika Fabiana [UNESP] (My University, 2008)
The need for a rational use of water and supply of food for a growing world population have led to the development of research in the area of irrigation systems. Thus, some irrigation systems which join efficiency with low cost of material have been developed. Although some technical characteristics are provided by the manufacturers, tests are required to verify functioning of the system and uniformity of water distribution. Continuous research on uniformity, characteristics of the materials and design of water distribution systems is essential for system improvement. Therefore, the objective of this work was to evaluate the CV (manufacturer's coefficient of variation) of Amanco microsprinkler (1.0 mm light green nipple) using bench testing in the laboratory of Irrigation at UNESP - FCA campus of Botucatu-SP. Twenty-five microsprinklers in a sequential design were used in the tests. Three flow systems were tested as follows: a Coil system based on serial connected pipes; a Lateral system, the most common system in which secondary lines are fed by a main line; and a Mesh system used in the urban water supply. The results showed that 4.17% CVf met the production standards and the Lateral and Mesh systems were similar regarding outflow using bench testing. The Mesh system presented the highest mean value of outflow and the lowest range of variation.
Evaluation of an amanco microsprinkler performance in a testing bench
Keywords: Bench testing; Manufacturer's coefficient of variation; Microsprinklers; System of distribution; Cost effectiveness; Equipment testing; Sprinkler systems (irrigation); benchmarking; design; distribution system; irrigation system; outflow; testing method; water supply; water use; Botucatu; Brazil; Sao Paulo [Brazil]; South America